2013
DOI: 10.4090/juee.2013.v7n2.253263
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Transport and Rainfall Erosivity Evolution in Twelve Basins in Central and Western Algeria

Abstract: Abstract:Soil erosion by rain and surface runoff is an important problem in the Mediterranean countries. The study of the relationship between erosion and sediment transport with hydrological and climatic factors have been conducted in many countries around the world. The aim of this work is to show rainfall impact on the variability of spatial and temporal concentration in twelve drainage basins in the west of Algeria. We will also seek to find a representative parameter of rainfall erosive potential on a Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
1
16
1
1
Order By: Relevance
“…This result agrees with those obtained in other areas of the Mediterranean basin (e.g. [75][76][77][78]), but is in contrast to findings in the Mediterranean Iberian peninsula, where some increase (+8.8%) of MFI was observed (e.g. [73]).…”
contrasting
confidence: 53%
“…This result agrees with those obtained in other areas of the Mediterranean basin (e.g. [75][76][77][78]), but is in contrast to findings in the Mediterranean Iberian peninsula, where some increase (+8.8%) of MFI was observed (e.g. [73]).…”
contrasting
confidence: 53%
“…These high plateaus narrow to the east due to their proximity with the Tell Atlas. Their elevation decreases to 400 m at Chott El Hodna (Meddi 2013). These highlands form natural barriers to rainproducing cloud masses (Laborde 1993;Meddi et al 2002) showed that much of the rainfall variability is explained by elevation and the landscape.…”
Section: Study Areamentioning
confidence: 94%
“…In the Tell Atlas plains, rainfall ranges from 500 in the west to 450 mm in the center and 700 mm in the east. In the Saharan Atlas, the climate is very hot and dry in summer and mild in winter, with lower rainfall compared to the north, owing to its greater distance from the sea (Meddi 2013). …”
Section: Climate and Rainfall Variabilitymentioning
confidence: 98%
See 2 more Smart Citations